Capital account regulation as part of the macroeconomic regime: comparing Brazil in the 1990s and 2000s - Barbara Fritz; Daniela Prates (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
Capital account regulation (CAR) has experienced profound reconsideration since the global financial crisis. This new debate focuses on the macroeconomic gains of regulating international capital flows in terms of reducing external and financial vulnerability, but it does not consider relevant aspects relating to the context in which these regulations are implemented. In this paper, we undertake a comparative analysis of similar types of CAR applied in Brazil during the 1990s and 2000s. Based on this analysis, we conclude that for the design of CAR, which is relevant for its effectiveness, institutional features of both the financial market and the macroeconomic regime, shaped by macroeconomic constraints, are relevant. For the case of Brazil, we conclude that, contrary to the 2000s, the strong preference given to inflation stabilization in the 1990s, together with high external vulnerability, strongly limited the CAR's design of this period.
Keywords: E6; F3; F4; F6; 330; macroeconomic regime; capital account regulation; capital flows; emerging economies